The quality of patient-nurse communication perceived before and during the COVID-19 pandemic: an Italian pilot study. : The quality of patient-nurse communication perceived and COVID-19 pandemic - Vitale, Elsa; Giammarinaro, Maria Pia; Lupo, Roberto; Archetta, Valeria; Fortunato, Rosa Silvia; Caldararo, Cosimo; Germini, Francesco (Acta Biomedica Atenei Parmensis, 2021)
Background and Aim of the work. Therapeutic communication is essential for assessing the quality of care of patients. The present study aimed how the forced use of the mask influenced the communication before and during the Covid-19 pandemic. Methods. An online questionnaire was administered including two socio-demographic items, such as sex, as male and female, and role, as nurse or patient, and the Quality of Communication Questionnaire (QOC) for twice, referring to the period before during the pandemic. Results. 178 subjects participated in the study, of which 60 (33.7%) were patients and 118 (66.3%) were nurses. During the pandemic, patients reported no significant differences in the perception of the quality of nurse-patient communication. While nurses recorded a lower perception of communication quality during the pandemic period than before. Conclusions. It emerged an urgent need to support the nursing activity from an organizational point of view, with less work overload, and psychological, with forms of help so that nurses could feel supported in the work fatigue, trying to give the best of himself.